What Happens When Individuals Answer Questionnaires in Two Different Languages - Paz, Clara; Hermosa-Bosano, Carlos; Evans, Chris (Frontiers in Psychology, 2021)
The aim of the present study was to compare scores from the English and the Spanish versions of two well-known measures of psychological distress using a within-subject approach. This method involved bilingual participants completing both measures in four conditions. For two groups of people, measures were offered in the same language both times and for the other two groups, each language version was offered, the order differing between the groups. The measures were the Clinical Outcomes in Routine Evaluation-Outcome Measure and the Schwartz Outcome Scale-10, both originally created in English and then translated to Spanish. In total, 109 bilingual participants (69.7% women) completed the measures in two occasions and were randomly allocated to the four conditions (English-English, English-Spanish, Spanish-English and Spanish-Spanish). Linear mixed effects models were performed to provide a formal null hypothesis test of the effect of language, order of completion and their interaction for each measure. The results indicate that for the total score of the Clinical Outcomes in Routine Evaluation-Outcome Measure just language had a significant effect, but no significant effects were found for completion order or the language by order interaction. For the Schwartz Outcome Scale-10 scores, none of these effects were statistically significant. This method offers some clear advantages over the more prevalent psychometric methods of testing score comparability across measure translations.